2019
DOI: 10.1016/j.ejps.2019.105059
|View full text |Cite
|
Sign up to set email alerts
|

Real-life budesonide and formoterol dose emission from the medium and high strength fixed dosed combinations in a Spiromax® dry powder inhaler using inhalation profiles from patients with chronic obstructive pulmonary disease

Abstract: Dry powder inhalers (DPIs) are passive devices used to administer inhaled medication for the management of asthma and chronic obstructive pulmonary disease (COPD). DPIs require patients to generate a sufficient internal turbulent airflow force during each inhalation to deaggregate the powdered drug formulation into an emitted dose containing particles with the greatest likelihood of lung deposition. This internal force is generated by the interaction between the user's inhalation flow and the resistance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…While current studies show clinical value of budesonide combined with tiotropium bromide in the treatment of COPD, 24 there is no unified standard for the optimal dosage of Budesonide. 15,16 Our study clearly shows that medium and high doses of Budesonide can improve disease treatment effect and ensure treatment safety. We may speculate that as the dosage of the medication increases, the local drug concentration rises, making it more effective in targeting the lesion and continuously exerting its efficacy.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…While current studies show clinical value of budesonide combined with tiotropium bromide in the treatment of COPD, 24 there is no unified standard for the optimal dosage of Budesonide. 15,16 Our study clearly shows that medium and high doses of Budesonide can improve disease treatment effect and ensure treatment safety. We may speculate that as the dosage of the medication increases, the local drug concentration rises, making it more effective in targeting the lesion and continuously exerting its efficacy.…”
Section: Discussionmentioning
confidence: 69%
“…The incidence of adverse reactions in both groups was low, which indicates the safety of high-dose budesonide. Bagherisadeghi et al 15 also confirmed that increasing the dosage of budesonide has certain positive impact on improving the pulmonary function rehabilitation effect of patients with COPD, and does not correlate with higher incidence of adverse reactions. Qi et al 16 showed that the optimal dose of budesonide for patients with COPD in China is 4-6 mg/d.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations